Basic Characteristics of Ionic Liquid-Gated Graphene FET Sensors for Nitrogen Cycle Monitoring in Agricultural Soil - Naoki Shiraishi; Jian Lu; Fatin Bazilah Fauzi; Ryo Imaizumi; Toyohiro Tsukahara; Satoshi Mogari; Shosuke Iida; Yusuke Matsukura; Satoshi Teramoto; Keisuke Yokoi; Izumi Ichinose; Mutsumi Kimura (Biosensors)
Nitrogen-based fertilizers are crucial in agriculture for maintaining soil health and increasing crop yields. Soil microorganisms transform nitrogen from fertilizers into <semantics><msubsup>NO3−</msubsup></semantics>–N, which is absorbed by crops. However, some nitrogen is converted to nitrous oxide (N2O), a greenhouse gas with a warming potential about 300-times greater than carbon dioxide (CO2). Agricultural activities are the main source of N2O emissions. Monitoring N2O can enhance soil health and optimize nitrogen fertilizer use, thereby supporting precision agriculture. To achieve this, we developed ionic liquid-gated graphene field-effect transistor (FET) sensors to measure N2O concentrations in agricultural soil. We first fabricated and tested the electrical characteristics of the sensors. Then, we analyzed their transfer characteristics in our developed N2O evaluation system using different concentrations of N2O and air. The sensors demonstrated a negative shift in transfer characteristic curves when exposed to N2O, with a Dirac point voltage difference of 0.02 V between 1 and 10 ppm N2O diluted with pure air. These results demonstrate that the ionic liquid-gated graphene FET sensor is a promising device for N2O detection for agricultural soil applications.